Kitosan sebagai Bahan Potensial Antikaries - Hakim, Enggardini (Jurnal Material Kedokteran Gigi, 2022)
Caries is a big challenge in dentistry. Chitosan is a non-toxic natural polysaccharide which has a good characteristic such as biocompatible, non-toxic, biodegradable, easily combined with other substances, and have antibacterial effect. Aim of this paper is to study the ability of chitosan to prevent dental caries. Chitosan has ability to inhibit the growth of cariogenic bacteria, prevent the formation of biofilms, encourage remineralization process and prevent demineralization. It can be concluded that chitosan has a great potency to be used as anticaries agent in dentistry.